2004
DOI: 10.1111/j.1471-4159.2004.02359.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of chronic neuroinflammation by a nitric oxide‐releasing derivative of the antioxidant ferulic acid

Abstract: Chronic neuroinflammation and oxidative stress contribute to the neurodegeneration associated with Alzheimer's disease and represent targets for therapy. Ferulic acid is a natural compound that expresses antioxidant and anti-inflammatory activities. Nitric oxide is also a key modulator of inflammatory responses. Grafting a nitric oxide-releasing moiety onto antiinflammatory drugs results in enhanced anti-inflammatory activity. We compared the effectiveness of ferulic acid with a novel nitric oxide-releasing de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 65 publications
4
56
0
Order By: Relevance
“…Also, apoptotic features such as fragmentation of DNA, alterations in mitochondria and a decreased Bax (proapoptotic) to Bcl-2 (antiapoptotic) ratio in cells treated with b-amyloid were attenuated by the T. aestivum L. extract (47). Apoptotic death of the SH-SY5Y cells exposed to Ab [25][26][27][28][29][30][31][32][33][34][35] , manifested by a decrease in the mitochondrial transmembrane potential, was blocked after pretreatment with the T. aestivum extract. Also, the intracellular accumulation of reactive oxygen species was diminished by the presence of the extract.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, apoptotic features such as fragmentation of DNA, alterations in mitochondria and a decreased Bax (proapoptotic) to Bcl-2 (antiapoptotic) ratio in cells treated with b-amyloid were attenuated by the T. aestivum L. extract (47). Apoptotic death of the SH-SY5Y cells exposed to Ab [25][26][27][28][29][30][31][32][33][34][35] , manifested by a decrease in the mitochondrial transmembrane potential, was blocked after pretreatment with the T. aestivum extract. Also, the intracellular accumulation of reactive oxygen species was diminished by the presence of the extract.…”
Section: Resultsmentioning
confidence: 99%
“…The b-amyloid-and scopolamine-treated mice showed increased reaction times in a spatial memory test (water maze test), but the application of the T. aestivum extract reversed this effect. The total dietary fibre from T. aestivum L. effectively inhibited an Ab [25][26][27][28][29][30][31][32][33][34][35] -induced decrease in the reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide. The authors concluded that the attenuation of the cytotoxicity and the memory deficits caused by scopolamine could be attributed to the presence of phenolic acids in T. aestivum L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…57,58 Previous studies implicated that both ferulic acid and caffeic acid modulated NO pathways in the central nervous system. [59][60][61] Increased central NO had a role of restraining sympathetic outflow, 50,62,63 thereby attenuating reflex tachycardia when arterial baroreceptors were unloaded due to blood pressure reduction. 58 Although the current data on CGAs are promising, gaps in knowledge remain to be filled.…”
Section: Molecular Targets Of Chlorogenic Acid In Blood-pressure Regumentioning
confidence: 99%
“…1), i.e., 4-(ONO2)butyl esters of flurbiprofen and naproxen, respectively. HCT-1026 has been under study for its therapeutic use in a variety of conditions, including neurodegeneration and inflammation (Keeble and Moore, 2002;Scatena et al, 2005;Gasparini et al, 2005;Prosperi et al, 2004;Wenk et al, 2004Wenk et al, , 2002Ronchetti et al, 2009;Idris et al, 2004). HTC-3012, as single (S)-enantiomer, has been tested in clinical trials for the treatment of osteoarthritis (Geusens, 2009;Zhang et al, 2011).…”
mentioning
confidence: 99%